2018
DOI: 10.1016/j.indcrop.2018.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration process influences the phenolic profile, antioxidant and antimicrobial properties of Galium aparine L.

Abstract: A B S T R A C TGalium aparine L. is a very disseminated plant in temperate zones, commonly known as clivers or bedstraw, belonging to the Rubiaceae family and it is traditionally used for its medicinal applications. In this study, G. aparine hydromethanolic extracts and infusions were prepared from air-dried and freeze-dried samples in order to assess their phenolic profile, antioxidant, antimicrobial, and cytotoxic properties. All the studied extracts revealed a similar phenolic profile, but the hydromethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Currently, numerous studies have demonstrated the effects of drying processes on extractable polyphenols (EPs) of fruits (Bustos, Rocha‐Parra, Sampedro, de Pascual‐Teresa, & León, ; Senio et al., ; Sukadeetad, Nakbanpote, Heinrich, & Nuengchamnong, ). However, a whole polyphenol fingerprint should include the EPs and nonextractable polyphenols (NEPs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, numerous studies have demonstrated the effects of drying processes on extractable polyphenols (EPs) of fruits (Bustos, Rocha‐Parra, Sampedro, de Pascual‐Teresa, & León, ; Senio et al., ; Sukadeetad, Nakbanpote, Heinrich, & Nuengchamnong, ). However, a whole polyphenol fingerprint should include the EPs and nonextractable polyphenols (NEPs).…”
Section: Introductionmentioning
confidence: 99%
“…However, the fresh loquat fruit is a perishable plant food as it contains a large proportion of water, leading to great economic losses (Elsafy, 2014;Zhou, Li, Sun, Xu, & Chen, 2011). Furthermore, loquat fruit harvest season is brief in the early summer and therefore the fresh fruit is not acquired throughout the Currently, numerous studies have demonstrated the effects of drying processes on extractable polyphenols (EPs) of fruits (Bustos, Rocha-Parra, Sampedro, de Pascual-Teresa, & León, 2018;Senio et al, 2018;Sukadeetad, Nakbanpote, Heinrich, & Nuengchamnong, 2018). However, a whole polyphenol fingerprint should include the EPs and nonextractable polyphenols (NEPs).…”
Section: Introductionmentioning
confidence: 99%
“…Significant antioxidant activity of ethanol, hexane, and ethyl acetate extracts obtained from G. brasiliensis, prepared by sonication, was reported by Saroni et al 9 The authors suggest that these results are due to the contribution of the redox-active bioflavonoid present in the extracts and several studies have also suggested a strong correlation between the antioxidant activity of medicinal plants and their phenolic composition. 3,20,21 The in vitro anti-inflammatory potential of each extract fraction was evaluated by measuring NO inhibition. The most effective fraction was the dichloromethane fraction (EC 50 , 83 ± 9 μg mL −1 ), closely followed by the hexane fraction (EC 50 , 112 ± 9 μg mL −1 ), and lastly by the ethyl acetate extract (EC 50 , 205 ± 9 μg mL −1 ).…”
Section: Bioactive Properties Of Individual Fractions Of G Brasiliensismentioning
confidence: 99%
“…Thus, medicinal plants have been recognized as an alternative medicine since ancient times. 3 The Amazon rainforest is present in nine countries of South America (Brazil, Peru, Colombia, Venezuela, Ecuador, Bolivia, Guyana, Suriname and French Guiana) with 60% present in the Brazilian territory. 4 Ethnopharmacological fieldstudies have identified several medicinal species popularly used for the treatment of a wide range of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Galium aparine L. is a herbaceous perennial plant belonging to the Rubiaceae family, widely grown in Europe and Asia ( Senio et al 2018). It is a natural antioxidant containing anthraquinones, iridoids, alkanes, flavonoids, tannins, polyphenolic acids and it is used in treatment of various diseases such as diabetes, cancer and hypertension (Saeed & Javed 2007).…”
Section: Introductionmentioning
confidence: 99%